Surgical Treatment for Achalasia of the Esophagus: Laparoscopic Heller Myotomy - Torres-Villalobos, Gonzalo (Hindawi Publishing Corporation, 2013)
Achalasia is an esophageal motility disorder that leads to dysphagia, chest pain, and weight loss. Its diagnosis is clinically suspected and is confirmed with esophageal manometry. Although pneumatic dilation has a role in the treatment of patients with achalasia, laparoscopic Heller myotomy is considered by many experts as the best treatment modality for most patients with newly diagnosed achalasia. This review will focus on the surgical treatment of achalasia, with special emphasis on laparoscopic Heller myotomy. We will also present a brief discussion of the evaluation of patients with persistent or recurrent symptoms after surgical treatment for achalasia and emerging technologies such as LESS, robot-assisted myotomy, and POEM.